2004
DOI: 10.4028/www.scientific.net/msf.471-472.162
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Cutting Temperature Measurements in High-Speed Machining

Abstract: High-speed machining has received important interest because it leads to an increase of productivity and a better workpiece surface quality. However, the tool wear increases dramatically in high-speed machining (HSM) operations due to the high cutting temperature at the tool-workpiece interface and chip-tool interface. Cutting temperature and its gradient play an important role in tool life and machined part accuracy. This paper reviews different methods of the measurements of cutting temperature, which includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…They also found that the analytical solutions by using relevant computer program were convenient and accurate. Wan et al (2004) summarized the present methods used to measure the cutting temperature, and analysed their merits and demerits and application ranges. Komanduri and Hou (2001c) also gave a review of the literature on several methods of temperature measurements.…”
Section: Nomenclaturementioning
confidence: 99%
“…They also found that the analytical solutions by using relevant computer program were convenient and accurate. Wan et al (2004) summarized the present methods used to measure the cutting temperature, and analysed their merits and demerits and application ranges. Komanduri and Hou (2001c) also gave a review of the literature on several methods of temperature measurements.…”
Section: Nomenclaturementioning
confidence: 99%
“…Tool wear is mainly caused by excessive temperatures in the heat zones which can be overcome by a suitable coating on the cutting tool [17]. Carbide coatings are known to impart better hot hardness and higher resistance to diffusion mechanism till 1100 °C, preventing the phenomenon of chip-welding to the tool rake surface [18].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been developed to solve the problem of thermal mapping of the cutting tool, workpiece and chips, for example: analytical methods [5] experimental and numerical (modeling) techniques [6], hybrid methods and techniques of the heat source. Several analytical models have been previously proposed by Merchant [7], which was developed by Oxley [8,9,10], latest works been adapted for the milling process [11].…”
Section: Introductionmentioning
confidence: 99%